Direct‐acting antivirals combination for elderly patients with chronic hepatitis C: A cost‐effectiveness analysis. (2nd March 2017) - Ciaccio, Antonio; Cortesi, Paolo A.; Bellelli, Giuseppe; Rota, Matteo; Conti, Sara; Okolicsanyi, Stefano; Rota, Monica; Cesana, Giancarlo; Mantovani, Lorenzo G.; Annoni, Giorgio; Strazzabosco, Mario
Abstract: Background: Chronic hepatitis C (CHC) has been undertreated among elderly patients. Interferon‐free treatment represents an opportunity for these patients. The aim of this study was to assess the cost‐effectiveness of directly acting antivirals (DAAs) in CHC elderly patients. Methods: A Markov model of CHC natural history was built. This study focuses on CHC patients older than 65 years, stratified according to genotype (1/4, 2 and 3), liver fibrosis (METAVIR F1 to F4), age and frailty phenotype (robust, pre‐frail and frail). DAAs combination vs no treatment was simulated for each theoretical population, assessing life years, quality‐adjusted life years (QALYs), costs, incremental cost‐effectiveness ratios (ICERs) in a lifetime time horizon and by the Healthcare System perspective. Results: Incremental cost‐effectiveness ratio increased with age and frailty status in all fibrosis stages. For robust F3 and F4 patients ICERs remained below the willingness‐to‐pay threshold (WTP) of 40 000€/QALY up to age 75 and 86 years, respectively, depending on drug price and sustained virological response probability (sensitivity analysis). Notably, in F4 and frail subjects older than 75 years, ICER was more sensitive to non‐liver‐related mortality rate. In elderly F1 and F2 patients, ICERs were below WTP only up to 77 years old, with wide variability among frailty phenotypes. Conclusions: Cost‐effectiveness of DAAs treatment of elderly CHC patients is solid in those with advanced fibrosis, but it depends strongly on frailty status and age, particularly in patients with milder fibrosis stages. Accurate assessment of clinical variables, including frailty, is necessary to allocate limited resources to this special population.